A) Développer les expressions suivantes :
F(x)=(2x+5)(3x-2) G(x)=(x+5)² - (3x-1)²
B) Factoriser les expressions suivantes:
H(x)=4x²+10x+25 I(x)=(x+3)² - (2x-5)² J(x)=(x+1)(3x-5)+(x+1)(1-4x)

2
F(x)=(2x+5)(3x-2) =6x²-4x+15x-10=6x²+11x-10
G(x)=(x+5)² - (3x-1)² =(x²-10x+25)-(9x²-6x+1)=x²-10x+25-9x²+6x-1=-8x²-4x+24
H(x)=4x²+10x+25 =(2x+5)²
I(x)=(x+3)² - (2x-5)² elle est déja factorisée
J(x)=(x+1)(3x-5)+(x+1)(1-4x)= (x+1)(3x-5+1-4x)=(x+1)(-x-4)

Réponses

2013-10-07T13:01:35+02:00
F(x)=(2x+5)(3x-2) =6x²-4x+15x-10=6x²+11x-10
G(x)=(x+5)² - (3x-1)² =(x²-10x+25)-(9x²-6x+1)=x²-10x+25-9x²+6x-1=-8x²-4x+24
H(x)=4x²+10x+25 =(2x+5)²
I(x)=(x+3)² - (2x-5)² elle est déja factorisée
J(x)=(x+1)(3x-5)+(x+1)(1-4x)= (x+1)(3x-5+1-4x)=(x+1)(-x-4)
2013-10-07T13:08:41+02:00
F(x) = (6x² - 4x +15x -10) = 6x² +11x -10
G(x) = (x+5-3x+1)(x+5+3x-1) = (-2x +6)(4x +4)
H (x) = (2x +5)²  identité remarquable
I(x) = (x+3-2x+5)(x+3+2x-5) = (-x+8)(3x -2)
J(x) = (x+1)(3x-5) + (1-4x) = (x+1)(3x-5+1-4x) = (x+1)(-x -4)